Referendums and citizen support for European integration - Christin, Thomas; Hug, Simon (2002)
A simple game-theoretic model suggests that voter preferences should find stronger reflection in policy outcomes if referendums are possible than if such popular influence is excluded. Relying on the large-scale quasiexperiments of European integration, we test whether referndums lead to more supportive voters with data covering more than 20 years. We find suggestive evidence for our theoretical implication that constitutional provisions for referendums lead to citizens more supportive of European integration. Similarly, the results suggest that voters more strongly support European integration immediately after a referendum vote. - Reproduced.
Keywords: European Union